2017
DOI: 10.1002/cmdc.201700635
|View full text |Cite
|
Sign up to set email alerts
|

LEGO‐Inspired Drug Design: Unveiling a Class of Benzo[d]thiazoles Containing a 3,4‐Dihydroxyphenyl Moiety as Plasma Membrane H+‐ATPase Inhibitors

Abstract: The fungal plasma membrane H+‐ATPase (Pma1p) is a potential target for the discovery of new antifungal agents. Surprisingly, no structure–activity relationship studies for small molecules targeting Pma1p have been reported. Herein, we disclose a LEGO‐inspired fragment assembly strategy for the design, synthesis, and discovery of benzo[d]thiazoles containing a 3,4‐dihydroxyphenyl moiety as potential Pma1p inhibitors. A series of 2‐(benzo[d]thiazol‐2‐ylthio)‐1‐(3,4‐dihydroxyphenyl)ethanones was found to inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…For over 25 years, only 17 notable studies of chemical agents targeting Pma1 for antifungal purposes were reported. Thioether: possible oxidation in the cell [34]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For over 25 years, only 17 notable studies of chemical agents targeting Pma1 for antifungal purposes were reported. Thioether: possible oxidation in the cell [34]…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, our group has reported an alternative drug design method based on the LEGO concept called: HFSA-SDOS (from hypothesis-based fragment selection and assembly (HFSA), specific biological relevant scaffold-based diversity-oriented synthesis (SDOS) to rational design) (Figure 17). [34] In this research, the combination of privileged-scaffolds selection and diversity-oriented synthesis has led to the identification of the series of benzo[d]thiazoles containing a 3,4dihydroxyphenyl moiety as potent Pma1 inhibitors. 16 compounds (68-83) were synthesized with IC 50 values ranging from 8 μM to 36 μM (Table 5).…”
Section: Lego-inspired Drug Design Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Azolium heterocycles are not only present in natural products, but also in countless substances of technical and medicinal importance. [16][17][18][19][20][21][22] The 2-thionated derivatives show valuable biological, e.g. anti-thyroid, properties.…”
Section: Introductionmentioning
confidence: 99%